Association of COL2A1rs2276454, rs1793953, COL9A1rs1135056, COL11A1rs1676486 structure-forming collagens of the nucleus pulposus with degeneration of intervertebral discs L5-L4, L5-S1 - Ye. H. Pedachenko; I. H. Vasylieva; M. V. Khyzhniak; O. S. Halanta; N. H. Chopyk; O. I. Tsiubko; A. B. Hriazov; O. S. Nekhlopochyn; T. A. Ksenzov; A. B. Dmytrenko; T. A. Makarova (Patologìâ)
Aim. The purpose of the work was to determine the relationship between degenerative changes of the L5-S1 and L4-L5 intervertebral discs with collagen mononucleotide variants COL2A1rs2276454, rs1793953, COL9A1rs1135056, COL11A1rs1676486 among ethnic Ukrainians.